Synthesis, morphology, characterisation and evaluation of carbon nanotubes-substituted YIG-PVA composites as electromagnetic wave absorbing materials - Beh, Hoe Guan (2011)
It is of interest whether carbon nanotubes (CNTs) and Yttrium Iron Garnet (YIG) containing polymer composite would produce any significant electromagnetic wave absorption effects in the composite. Therefore, in this work, carbon nanotubes-substituted YIG-PVA composites (YIG(La)-CNTs-PVA and YIG(Bi)-CNTs-PVA composites) were fabricated. Morphology and its electromagnetic properties as electromagnetic wave materials were studied. Yttrium iron garnet (YIG) substituted with lanthanum and bismuth namely Y3-xLaxFe5O12 and Y3-xBixFe5O12 (where x=0.0, 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0) were synthesized via sol gel technique. The phase formation, surface morphology and magnetic properties of as-prepared YIG nanoparticles were studied using X-Ray diffraction (XRD), transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM), respectively. The synthesized single phases YIG(La) and YIG(Bi) particles have spherical shapes with particles size in the range of 35-80nm. The saturation magnetization of YIG(La) and YIG(Bi) were 17.72emu/g and 18.57emu/g, respectively. Carbon nanotubes (CNTs)which are used as filler for the composites were synthesized by the decomposition of methane over Co-Mo/MgO catalyst using chemical vapor deposition (CVD) technique. The ratio of Co to Mo supported on MgO and the catalytic reaction time were studied to optimize a CNTs yields. The optimization of CNTs yields was obtained by using the Co:Mo catalyst at ratio 1:1 supported on MgO and the catalytic reaction time of 180min. The microstructure and particles sizes of as-prepared CNTs were determined using TEM. 6M HNO3 and 6M H2SO4 in a volume ratio of 1:3 were used to purify and functionalise the as-prepared CNTs. The purity of CNTs and the functional group introduced on CNTs after purification were determined by using Thermogravimetric Analysis (TGA) and identifying the groups using Fourier Transform Infrared Spectroscopy (FTIR), respectively. High purity CNTs of about 98.57% together with COOH and OH functional groups were obtained after purification process. The highest dielectric loss of CNTs-PVA composite was obtained with addition 3wt% of CNTs, while the highest dielectric and magnetic losses of YIG(La)-CNTs-PVA and YIG(Bi)-CNTs-PVA composites were obtained when 3wt% of CNTs were used. The highest tan δ obtained at YIG(La)-CNTs-PVA and YIG(Bi)-CNTs-PVA were 6.75 at frequency 100MHz and 1.12 at frequency 300MHz, respectively. It is suggested that the dielectric loss of the composites understudied are due to the interfacial polarisation of YIG(Bi) or YIG (La), CNTs and PVA within composite and magnetic losses are due to the domain wall movement of YIG(La) or YIG(Bi) in composite.